2019
DOI: 10.1186/s13007-019-0416-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grain yield based on digital images of rice canopy

Abstract: BackgroundRice canopy changes are associated with changes in the red light (R), green light (G), and blue light (B) value parameters of digital images. To rapidly diagnose the responses of rice to nitrogen (N) fertilizer application and planting density, a simple model based on digital images was developed for predicting and evaluating rice yield.ResultsN application rate and planting density had significant effects on rice yield. Rice yield first increased and then decreased with increasing of N rates, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…can describe plant color [28], which can reflect its nutrient status, especially N content and absorption. Several studies have shown that RGB color space parameters extracted from vegetation canopy images can be used to predict vegetation yield and nutrient status [15,19,20]. Among the models constructed with image parameters in this study, those constructed using NRI were unstable, possibly because the parameters of NRI were obtained by extracting RGB values from images.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 91%
See 1 more Smart Citation
“…can describe plant color [28], which can reflect its nutrient status, especially N content and absorption. Several studies have shown that RGB color space parameters extracted from vegetation canopy images can be used to predict vegetation yield and nutrient status [15,19,20]. Among the models constructed with image parameters in this study, those constructed using NRI were unstable, possibly because the parameters of NRI were obtained by extracting RGB values from images.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 91%
“…Digital cameras are a common and inexpensive piece of equipment. They can collect image and spectral information with sufficient quality to use in predictions of crop nutrition status [13,14] and yield [15] [16], and to monitor pests [17]. Li et al extracted the dark green color index (DGCI) of image features, and concluded that DGCI was significantly correlated with the SPAD value of rice leaves.…”
Section: Introductionmentioning
confidence: 99%
“…constructed a regression model of a maize N nutrition index using a dual-band spectral index (R710, R512) [24], and it was proven to be a can describe plant color [25], which can reflect its nutrient status, especially N content and absorption. Several studies have shown that RGB color space parameters extracted from vegetation canopy images can be used to predict vegetation yield and nutrient status [14,18,19]. Among the models constructed with image parameters, those constructed using NRI and GMR were unstable, possibly because the parameters of NRI and GMR were obtained by extracting RGB values from images.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 99%
“…Digital cameras are a common and inexpensive piece of equipment. They can collect image and spectral information with sufficient quality to use in predictions of crop nutrition status [12,13] and yield [14] [15], and to monitor pests [16]. Li et al extracted the dark green color index (DGCI) of image features, and concluded that DGCI was significantly correlated with the SPAD value of rice leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Instruments for N diagnosis include a chlorophyll meter, spectrometer, unmanned aerial vehicle, and digital camera 3 8 . However, the above methods and instruments have some limitations in N diagnosis, as they are time-consuming, destructive, and expensive 9 , 10 . Barbedo found that close-range images can be used to detect visual changes in plant color and morphology and machine learning techniques become an effective solution 11 .…”
Section: Introductionmentioning
confidence: 99%